2020
DOI: 10.1111/jdi.13400
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for abnormal postpartum glycemic states in women diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria

Abstract: Aims/Introduction: To evaluate the rate of postpartum glycemic screening tests (PGST) in women with gestational diabetes mellitus (GDM), and to investigate risk factors for abnormal PGST results. Materials and Methods: We retrospectively analyzed the obstetric data of 1,648 women with GDM who gave birth after 28 completed weeks of gestation between 1 July 2011 and 31 December 2019 at Taipei Chang Gung Memorial Hospital, Taiwan. GDM was diagnosed by the International Association of Diabetes and Pregnancy Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…24,25 Thus, it has been reported that older maternal age and insulin requirement were risk factors for post-partum glucose metabolism disorder, whereas high pre-gestational BMI and elevated fasting plasma glucose at GDM diagnosis were the major predictors for prediabetes. 26,27 In the present study, the level of HbA1C was not associated with a significant risk of postpartum prediabetes, and BMI was not included in the regression model because of substantial missing data. Older age as a factor for A2GDM: The age category ≥45 years had the highest prevalence of insulin requirement (42.9%) versus 17.4% and 22.5% in those aged <35 years and 35-44 years, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…24,25 Thus, it has been reported that older maternal age and insulin requirement were risk factors for post-partum glucose metabolism disorder, whereas high pre-gestational BMI and elevated fasting plasma glucose at GDM diagnosis were the major predictors for prediabetes. 26,27 In the present study, the level of HbA1C was not associated with a significant risk of postpartum prediabetes, and BMI was not included in the regression model because of substantial missing data. Older age as a factor for A2GDM: The age category ≥45 years had the highest prevalence of insulin requirement (42.9%) versus 17.4% and 22.5% in those aged <35 years and 35-44 years, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…[ 12 ] In a prospective cohort study of 493 women with GDM screened at 6 to 12 weeks postpartum, the history of fetal death was higher in women with PPpreDM. [ 13 ] Higher blood sugars at diagnosis of GDM are associated with persistent postpartum hyperglycemia,[ 14 15 ] and women with fetal death are more likely to have uncontrolled GDM. Previous history of fetal demise was a risk factor for PPDM in our study but not for prediabetes [ Table 2 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Similar findings have been reported in other studies as well,[ 6 ] while some have failed to report a difference. [ 13 ]…”
Section: Risk Factorsmentioning
confidence: 99%